EFEKTIVITAS MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN WORDWALL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI PERKALIAN KELAS 4 SDN KARANG TANJUNG - Nahdliyah Jadidah; Muhammad Assegaf Baalwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The analysis shows that students' mathematical abilities are inadequate. Available data indicate that 25 out of 29 fourth-grade students have limited abilities. This condition is caused by the application of traditional teaching methods, in which teachers rely too much on teaching materials in the form of reading texts without considering the adequate use of other teaching materials. This situation results in passive attitudes and a lack of willingness to participate in the learning process. This study aims to analyze the effectiveness of the Game-Based Learning (GBL) model combined with Wordwall media. The main objective of this study is to test the effectiveness of the GBL model in solving math problems at the junior high school level at SDN Karangtanjung. In this study, a quantitative experiment was conducted using a pre- and post-test method. The research sample consisted of 29 fourth-grade students at SDN Karangtanjung. In this study, a narrative test instrument with ten questions was developed. The term “test questions” is associated with the indicator “problem-solving competence” as defined by Polya. In this study, a comparative analysis (Paired-Sample-t-Test) was conducted to analyze the data. The study concluded that the combination of the GBL (Game-Based Learning) model with the Wordwall medium can significantly improve mathematical problem-solving competence. The hypothesis proposed was confirmed significantly, as indicated by the significance test (Sig. 2-tailed) with a result of 0.000 < 0.05. This study concludes that the Wordwall model is an effective method for improving students' mathematical abilities in the field of multiplication.